Cultural Diversity A Glimpse Over the Current Debate in Sweden - Kiflemariam Hamde (Fondazione Eni Enrico Mattei (FEEM), 2006)
A year and a half ago, the Swedish government decided 2006 to be The Year for Cultural Diversity (Agenda för Mångkultur, 2005). The general purpose, according to the directive, is to facilitate the possibilities for all citizens to participate in all aspects of the cultural life by enhancing appropriate arenas for different traditions (Agenda för Mångkultur, 2005). This policy decision was not a surprise to both observers and participants of the diversity debate. There has been a growing interest in the virtues of diversity for business effectiveness and success (mångfald.com), heightened scrutiny of institutional and organizational life by the mass media, and legitimizing debates by political parties which had always had some form of concern for diversity, if not for its own sake, at least for capitalizing on the legitimacy of diversity politics in the expectation of local and parliament elections next September. The proclamation of 2006 as a Year for Cultural diversity thus comes naturally from the broadened debates and organizational programs, each actor trying to get legitimacy by using the concept of cultural diversity to suit the demands of the times. Indeed, cultural diversity has become a priority agenda for any legitimate actor, at least in terms of programs and polices, if not in action. Moreover, the coordinator of the 2006 Cultural Year consistently promised in the mass media that this would be the starting point, and not merely a celebratory performance (VK, 28 October 2005; DN 3 January 2006). Already, what are called as the Cultural diversity consultants had worked since 2003 in eight counties as a partial preparation for this year, and to raise the consciousness of relevant actors in the field of culture and cultural institutions, especially those financed by state money. Private cultural associations, however, are invited to participate during the diversity year but they were not invited to co-design the contents of the diversity year. This paper is concerned with describing the concept of diversity as used by the different actors in this context, and also examines the background that has led to the decision of the Cultural Year. An implicit concern is scrutinizing whether in fact this year would be a starting point for more deeply engaged diversity programs and actions or a symbolic act of window dressing. The concerned actors base the paper on accounting the background to the Diversity debate in Sweden, and the different expected programs and agendas. As such, the paper is based on analysis of documents and agendas, interviews with different actors and two multicultural consultants at the county level. Additionally, the author also participated in a couple of seminars and conferences and video-filmed some of the speeches by different presenters to capture the patterns of the debate/discourse on Cultural diversity. Implicit discussion is whether the current interest on diversity may lead to its institutionalization in the Swedish society organizations (Scott 1995, Hamde, 2002), or it simply is a traveling idea to appear occasionally and then occur in fashion-like manner as many management ideas (Czarniawska & Joerges, 1996). As pointed out in the sub-title this paper brings provides only a mere glimpse at the huge subject and the debate.
Keywords: 330; : Actors; cultural diversity; institutionalization; multicultural consultants; multicultural year; Swedish debate